Advanced Structural and Functional Materials. - Chun, Sangeun; Salem, Abdel-Badeeh Mohamed; Gorlatch, Sergei (Trans Tech Publications, Limited, 2021)
Special topic volume with invited peer-reviewed papers only.
Description based upon print version of record.
Keywords: Materials -- Congresses.; Building materials -- Congresses.; Composite materials.; Matériaux -- Congrès.; Construction -- Matériaux -- Congrès.; Composites.; composite material.; Building materials; Materials; Conference papers and proceedings